Effect of massage therapy on infants with congenital muscular torticollis: A retrospective comparative study - Tang, Wei; Li, Zhoujin; Xu, Weihui; Ye, Yong; Wang, Huijuan; Wang, Ying; Shao, Xiangning; Wang, Mengqing; Xu, Jianda (Frontiers in Pediatrics, 2023)
Objective: To detect the effect and safety of massage therapy in infants with congenital muscular torticollis. Methods: A total of 56 infants with unilateral congenital muscular torticollis were enrolled in this retrospective comparative study. The control group (n=28) got the sternocleidomastoid (SCM) stretching, while the massage group (n=28) received massage therapy combined with SCM stretching. The following parameters were compared: cervical range of motion (ROM) and functional level (muscle function scale and ratio of muscle function scale scores). Complications were also recorded. Results: Of the 56 infants, 7 infants (12.5%) underwent surgery with little functional improvement. The total effective rate of conservative treatment is 87.5%. No significance was found about the surgery rate between both groups (14.29 Vs 10.71%, P=0.693). After treatment, the ROM (including rotation and lateral flexion) and the ratio of muscle function scale scores improved significantly (P<0.05). At latest followed up, massage group showed greater improvement in rotation and lateral flexion. However, no significant difference in muscle function scale scores ratio was found (P=0.126). None adverse events related to blood vessels, nerves and SCM occurred. Conclusions: Adding massage therapy in infants with congenital muscular torticollis is a safe and effective method to improve cervical range of motion and function. However, the decrease of surgical rate isn’t found in present study.